PENGARUH FRAUD TRIANGLE TERHADAP FRAUDULENT FINANCIAL STATEMENT DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Yuni Widawati; Adam Zakaria; Petrolis Nusa Perdana (Universitas Muhammadiyah Tangerang, 2022)
Fraudulent financial statement is a form of fraud that causes losses to stakeholders. Recently, fraudulent financial statement has been rampant in the financial and banking industry, which has caused the financial and banking industry to be the sector that suffered the most losses due to fraudulent financial statements. The purpose of this study is to examine factors that influence fraudulent financial statements using the fraud triangle approach. The object of this research is banking companies listed on Indonesia Stock Exchange in period of 2017-2019. This study used 102 samples taken using purposive sampling method. Data analysis was performed using panel data regression. The result of this study indicates that rationalization has significant effect on fraudulent financial statements, while financial target and effective monitoring have no significant effect on fraudulent financial statements. In addition, this study shows that corporate governance can weaken the influence of financial target, ineffective monitoring and rationalization of fraudulent financial statements.